Higher-rank tensor non-Abelian field theory: Higher-moment or subdimensional polynomial global symmetry, algebraic variety, Noether's theorem, and gauging - Juven Wang; Kai Xu; Shing-Tung Yau (Physical Review Research, 2021)
With a view toward a fracton theory in condensed matter, we introduce a higher-moment polynomial degree-p global symmetry, acting on complex scalar/vector/tensor fields (e.g., ordinary or vector global symmetry for p=0 and p=1 respectively). We relate this higher-moment global symmetry of n-dimensional space, to a lower degree [either ordinary or higher-moment, e.g., degree-(p-ℓ)] subdimensional or subsystem global symmetry on layers of (n−ℓ)-submanifolds. These submanifolds are algebraic affine varieties (i.e., solutions of polynomials). The structure of layers of submanifolds as subvarieties can be studied via mathematical tools of embedding, foliation, and algebraic geometry. We also generalize Noether's theorem for this higher-moment polynomial global symmetry. We can promote the higher-moment global symmetry to a local symmetry and derive a new family of higher-rank-m symmetric tensor gauge theory by gauging, with m=p+1. By further gauging a discrete Z_{2}^{C} charge conjugation (particle-hole) symmetry, we derive a general class of rank-m tensor non-Abelian gauge field theory (the gauge structure is noncommutative thus non-Abelian but not an ordinary group): a hybrid class of (symmetric or nonsymmetric) higher-rank-m tensor gauge theory and antisymmetric tensor topological field theory, generalizing Wang and Xu [Ann. Phys. 424, 168370 (2021)APNYA60003-491610.1016/j.aop.2020.168370], interplaying between gapless and gapped sectors.